Performance of blood concentrates in controlling inflammatory signs and symptoms after lower third molar extractions: an overview - de Almeida, Vinícius Lima; de Assis Costa, Marcelo Dias Moreira; Mesquita, Caio Melo; Vieira, Walbert Andrade; Lima, Rafael Rodrigues; Lima, Livia Bonjardim; Rode, Sigmar de Mello [UNESP]; Paranhos, Luiz Renato (FapUNIFESP (SciELO), 2025)
Purpose: To summarize the available evidence and answer the following question: What is the current knowledge on the performance of blood concentrates in handling sequelae after lower third molar extractions with the evidence available in systematic reviews? Methods: An electronic search was conducted across nine databases. The study included systematic reviews with or without meta-analyses investigating the performance of blood concentrates in managing sequelae after lower third molar extractions. The four outcomes analyzed were pain, edema, mouth opening, and alveolar osteitis. The AMSTAR-2 tool assessed the methodological quality of the included systematic reviews, while ROBIS evaluated the risk of bias. Results: The electronic search revealed 690 records, of which 15 were eligible systematic reviews for the present study. Overall, these reviews evaluated 75 primary studies published from 2007 to 2023. According to AMSTAR-2, only one systematic review presented high methodological quality. The ROBIS tool showed two systematic reviews with a low risk, and the others had a high risk of bias. Conclusion: The current evidence is based on only one systematic review with high methodological quality and a low risk of bias, while the others exhibited a high risk of bias and low methodological quality. Therefore, the evidence regarding the efficacy of blood concentrates in controlling sequelae following lower third molar extractions is inconclusive.
Keywords: Inflammation; Platelet-Rich Fibrin; Platelet-Rich Plasma; Systematic Review